Incorporating clonality into the plant ecology research agenda. (December 2021) - Klimešová, Jitka; Ottaviani, Gianluigi; Charles-Dominique, Tristan; Campetella, Giandiego; Canullo, Roberto; Chelli, Stefano; Janovský, Zdeněk; Lubbe, F. Curtis; Martínková, Jana; Herben, Tomáš
Abstract : A longstanding research divide exists in plant ecology: either focusing on plant clonality, with no ambition to address nonclonal plants, or focusing on all plants, ignoring that many ecological processes can be affected by the fact that some plants are clonal while others are not. This gap cascades into a lack of distinction and knowledge about the similarities and differences between clonal and nonclonal plants. Here we aim to bridge this gap by identifying areas that would benefit from the incorporation of clonal growth into one integrated research platform: namely, response to productivity and disturbance, biotic interactions, and population dynamics. We are convinced that this will provide a roadmap to gain valuable insights into the ecoevolutionary dynamics relevant to all plants. Highlights: Clonal plants can represent a substantial proportion of species in floras and plant communities. Because they share several functions that are not present in nonclonal plants, the differences in their proportions are likely to scale up as community and ecosystem differences. Clonal reproduction is provided by specialized organs that directly or indirectly affect other plant traits. Clonal growth organs usually serve for the storage of carbohydrates and the buildup of the bud bank, both necessary for resprouting in recurrently disturbed habitats. These storage organs affect global carbon cycling. Clonal growth leads to increased plant size in the horizontal dimension and to different degrees of ramet aggregation that influence the exploration of soil resources, pollination, and biotic interactions. Clonal growth serves as a reproductive insurance mechanism that further affects plant demography and possible evolutionary rates.